(untitled) (Current Horticulture, 2024)
Mango (Mangifera indica) is the most important fruit crop of India with high potential in export and foreign exchange. An impediment in mango fruits export has been the infestation by Bactrocera dorsalis (Hendel) and B. zonata (Saunders). The adoption of pre-harvest Integrated Pest Management (IPM) developed by ICAR-Indian Institute of Horticultural Research (IIHR) reduced infestation by 95% (Stonehouse et al., 2005, Verghese et al., 2002). Subsequent improvement of pre-harvest control using ovipositional deterrence gave more than 98% control (Verghese et al., 2020). However, for exports, 100% disinfestation is mandatory. For the most part, postharvest pest control is focused on trade and exports. In order to achieve safe post harvest disinfestation several experiments and studies were conducted on main commercial varieties using hot water (45oC to 48oC), for different lengths of time to standardize the thermal disinfestation protocol which is internationally acceptable (Yahia and Campos, 20. All the studies were conducted at ICAR-IIHR where orchards of major export mango varieties are available.